Optimalisasi Temu Kembali Informasi Dengan Teknologi Kecerdasan Buatan di Perpustakaan - Sari, Kartika Puspita; Masruri, Anis; Rosalia, Desfiana Ramdhani (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2023)
The purpose of this research is to describe how information retrieval using artificial intelligence in STIPRAM Yogyakarta library is optimal because artificial intelligence (AI) technology has been widely used in libraries to optimize information retrieval and improve user experience. This research method is descriptive and qualitative, and uses observation and interview techniques. The results of this study indicate that artificial intelligence in the STIPRAM library is very influential for users so that it can help users and librarians in conducting research and work more easily because information retrieval in the STIPRAM library can work optimally